An extensive analysis on the procurement process of consumer healthcare of GlaxoSmithKline Bangladesh - Imtiaz, Asif (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.